IL-18 biology in severe asthma - Thawanaphong, Sarita; Nair, Aswathi; Volfson, Emily; Nair, Parameswaran; Mukherjee, Manali (Frontiers in Medicine, 2024)
The role of interleukin-18 (IL-18) and inflammasomes in chronic inflammatory airway diseases, such as asthma and chronic obstructive pulmonary disease (COPD), has garnered significant attention in recent years. This review aims to provide an overview of the current understanding of IL-18 biology, the associated signalling pathways, and the involvement of inflammasome complexes in airway diseases. We explore the multifaceted role of IL-18 in asthma pathophysiology, including its interactions with other cytokines and contributions to both T2 and non-T2 inflammation. Importantly, emerging evidence highlights IL-18 as a critical player in severe asthma, contributing to chronic airway inflammation, airway hyperresponsiveness (AHR), and mucus impaction. Furthermore, we discuss the emerging evidence of IL-18's involvement in autoimmunity and highlight potential therapeutic targets within the IL-18 and inflammasome pathways in severe asthma patients with evidence of infections and airway autoimmune responses. By synthesizing recent advancements and ongoing research, this review underscores the importance of IL-18 as a potential novel therapeutic target in the treatment of severe asthma and other related conditions.